2004
DOI: 10.1536/jhj.45.845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA Damage in Lymphocytes of Cardiologists Exposed to Radiation During Cardiac Catheterization by the COMET ASSAY

Abstract: SUMMARYThis study was designed to evaluate the possible in vivo induction of DNA damage by exposure to radiation in cardiologists. The alkaline comet assay (single cell gel electrophoresis, SCGE), which appears to be a promising tool with which to estimate DNA damage at the single cell level, has been used. The assay was carried out on 30 cardiologists currently employed in a busy cardiac service and 30 healthy unexposed controls. Venous blood samples were obtained from the exposed and control subjects and SCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…From the 56 studies remaining, 19 further studies failed these conditions. Fourteen of the latter studies only reported the result of a statistical test (P-value) for appropriate group comparison (122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135). These studies are summarized in a separate table (Table I) and will be considered in the discussion.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…From the 56 studies remaining, 19 further studies failed these conditions. Fourteen of the latter studies only reported the result of a statistical test (P-value) for appropriate group comparison (122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135). These studies are summarized in a separate table (Table I) and will be considered in the discussion.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…We present here a sample of studies attempting to represent both the types of radiation-exposed occupations and different countries where this issue has been tested. Boyaci et al (2004) found a higher percentage of damaged cells (using the comet method) in cardiologists exposed to radiation of catheterization compared to controls. Goloni-Bertollo, Tajara, Manzato, and Varella-Garcia (1992) found a higher rate of sister chromatid exchanges and chromosomal aberrations in nurses handling antineoplastic agents compared to nurses not exposed to such agents and to age-and sex-matched controls.…”
Section: Radiation and Dna Damagementioning
confidence: 85%
“…Some studies have reported elevated DNA damage among interventional cardiologists exposed to prolonged and cumulative radiation exposure, suggesting the need for adequate measures to protect and prevent health care personnel who work in areas of prolonged radiation exposure [24] . Another study reported significant DNA damage as measured by increase in comet tail length after a work day of occupational exposure among nuclear medicine and radiology workers [11] .…”
Section: Main Findingsmentioning
confidence: 99%